Property rights: Issues and challenges - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Rights over land and other natural resources play a fundamental role in human society. The distribution of wealth and poverty is a reflection of underlying property rights. However, reforming property rights to give poor women and men greater access and stronger control over resources is not an easy task.